Environmental Value and Pro-environmental Behavior Among Young Adults: The Mediating Role of Risk Perception and Moral Anger - Li, Xin; Liu, Zhenhui; Wuyun, Tena (Frontiers in Psychology, 2022)
This study aims to identify the relationship between students’ environmental value (EV) and pro-environmental behavior (PEB) within a values-belief-norm framework. To conduct an empirical study, we used a sample of 558 online surveys and adopted the partial least squares path modeling method to test the relationships between variables in the conceptual model. The results indicate that EV positively predicted PEB among young adults. In addition, we highlight that risk perception (RP) and moral anger (MA) play critical chain mediating roles in the relationship between EV and PEB. This study has meaningful implications for practitioners seeking to encourage the public’s ecofriendly behavior by suggesting ways to encourage RP and stimulate individuals’ moral emotions about the environment.